FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PENGGUNAAN KONDOM DAN PELICIN PADA KELOMPOK GAY DALAM UPAYA PENCEGAHAN HIV/AIDS DI KOTA SEMARANG - Yustina Hartiana Limasale; VG Tinuk Istiarti; Syamsulhuda Budi Musthofa (Jurnal Kesehatan Masyarakat (Undip), 2017)
In 2015 Central Java was in the 3rd rank of the most HIV/AIDS cases out of 10 province in Indonesia and in the last 3 years, HIV cases in Semarang City tend to increase. Man groups contribute 58% of HIV cases in Semarang.  LSL (man to man sex) is one of the key population and classified as gay, which is someone whose sexual orientation and behavior only with man. A risky sexual intercourse and inconsistency of condom and lubricant usage are the reasons of a high HIV transmission in gay group. The purpose of this research was to analyze the factors related to practice of condom and lubricant use in gay groups in prevention of HIV/AIDS in Semarang City. This was an analytical descriptive research with quantitative and qualitative approach and cross sectional design study. Population of the research was gay in the shelter of PKBI Semarang City with the total of 630 people then 84 samples were taken using accidental sampling when gay was doing VCT test in Health Center and 2 informants with purposive sampling to complete the qualitative data. Data was collected by interviewing with questionnaire and interview guideline. Data analysis was using univariate and bivariate with chi-square test with 95% significance level. The results showed that dependent variable which related to practice of condom and lubricant use were knowledge (p=0,003), attitude (p= 0,001), and support from sexual partner (p= 0,013). Results of the qualitative research indicated that both of the informants were not consistent in using condom and lubricant were because they trusted their sexual partners whether they were permanent or not that they were free from disease.